Gagasan Penting untuk Mengetahui Apa itu Transaksi Gharar - M. Miftahur Rahmat Isnaini; Ahmadih Rojalih Jawab (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2023)
There is a system of uncertainty known as Gharar in muamalah, or buying and selling. A thorough understanding of the several types of gharar is necessary to recognize, prevent, or mitigate its effects in transactions. Gharar can arise in a variety of ways and circumstances. Specifically, theories from various literatures related to this research were understood and studied as part of the qualitative research process. To collect data, various sources were sought and reconstructed, including books, newspapers, magazines, archives, journals, notes, and other materials related to the idea of Gharar. All buying and selling activities that involve risk, betting, or gambling are considered gharar. It is expected to avoid transactions that contain gharar.